2023
DOI: 10.1039/d3ce00354j
|View full text |Cite
|
Sign up to set email alerts
|

Novel cyclam multicomponent crystal forms: synthesis, characterization and antimicrobial activity

Rajaa Saied,
Paula C. Alves,
Patrícia Rijo
et al.

Abstract: Novel multicomponent crystal forms were obtained from reactions of trans-disubstituted cyclam derivatives with flufenamic and salicylic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Cyclams are macrocyclic polyamines which have demonstrated medical interest, namely as antibacterial, antifungal and antiparasitic agents [18][19][20][21][22][23][24][25][26]. The cyclam salt H 4 [H 2 ( 4-CF3 PhCH 2 ) 2 Cyclam]Cl 4 (compound 1) was previously studied against C. krusei and C. albicans, and demonstrated a relevant antifungal activity, with minimal inhibitory concentration (MIC) values of 8 µg/mL for C. krusei and of 128 µg/mL for C. albicans [7].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclams are macrocyclic polyamines which have demonstrated medical interest, namely as antibacterial, antifungal and antiparasitic agents [18][19][20][21][22][23][24][25][26]. The cyclam salt H 4 [H 2 ( 4-CF3 PhCH 2 ) 2 Cyclam]Cl 4 (compound 1) was previously studied against C. krusei and C. albicans, and demonstrated a relevant antifungal activity, with minimal inhibitory concentration (MIC) values of 8 µg/mL for C. krusei and of 128 µg/mL for C. albicans [7].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclams are macrocyclic polyamines, the medical interest in which was fueled by the therapeutic potential of a bicyclam derivative against HIV infection, inflammatory diseases, cancer, and stem-cell mobilization [ 1 ]. Taking advantage of their biocompatibility, high metal chelation stability constants, and the possibility of N-functionalization of the cyclam backbone, a variety of cyclam derivatives have been successfully explored in recent years as antibacterial [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ], antifungal [ 7 , 8 , 9 ], and antiparasitic agents [ 10 , 11 , 12 ]. The neamine cyclam derivative (NeaCyclam) was revealed to be highly effective against Escherichia coli and Enterococcus aerogenes , being able to affect the outer membrane stability by altering the permeability barrier [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the inhibitory effect was maintained against clinical isolates of M. tuberculosis resistant to single or multiple antimycobacterial drugs. A series of trans -disubstituted cyclam salts displaying benzyl groups directly attached to the cyclam ring was found to be active against E. coli and Staphylococcus aureus [ 6 , 7 ]. The results obtained revealed that the position and polarity of the substituents on the benzyl groups attached to the cyclam ring are directly related to the antibacterial activity, with the compound displaying a CF 3 moiety in the para position of the benzyl groups being remarkably active.…”
Section: Introductionmentioning
confidence: 99%